Policy Frameworks for Enhancing Agricultural Marketing Strategies: Case Study of Chomphet District, Luang Prabang Province, Lao PDR - Sylilertmany, Khamkeo; Lattanasouvannaphonh, Champa; ThummKhamkeo achuck, Sivay; Silivong, Chitchai; Sengsoulichanh, Chanthachone (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This study examines the potential markets and policy frameworks to enhance agricultural marketing strategies in Chomphet District, Luang Prabang Province, Lao PDR. Employing a mixed-methods design, including surveys of 42 grocery shops in Luang Prabang City and Focus Group Discussions (FGDs) with representatives from 12 villages, the research identifies strengths, weaknesses, opportunities, and threats (SWOT) associated with production capacity and market access. Findings indicate strong demand for agricultural and artisanal products, driven by the district’s strategic proximity to the UNESCO World Heritage city of Luang Prabang. The study employs a TOWS Matrix to formulate SO, ST, WO, and WT strategies, providing actionable guidance for sustainable marketing development and inclusive economic growth.